2014
DOI: 10.1039/c3dt53141d
|View full text |Cite
|
Sign up to set email alerts
|

Turn-on trivalent cation selective chemodosimetric probe to image native cellular iron pools

Abstract: A new turn-on cell permeable chemodosimetric probe has been developed and its application in the selective detection of trivalent cations (Fe(3+)/Cr(3+)/Al(3+)) at a sub-nanomolar level has been demonstrated. The selectivity of over a broad spectrum of mono- and divalent metal ions was established using fluorescence spectroscopy. Moreover, the changes in the absorption spectra of in the presence of trivalent cations enabled the most bio-relevant metal ion Fe(3+) over Cr(3+)/Al(3+) to be distinguished. The prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The LOD were in the mM range and were similar to those calculated for other recently published probes for trivalent cations. [9][10][11][12][13][14][15][16][17][18][19][20][21] Moreover, we also found that water-acetonitrile 95 : 5 v/v solutions of 3 showed, when excited at 300 nm, an intense emission band at 397 nm. From all the cations tested, only the addition of Cr 3+ , Fe 3+ , Al 3+ , Ga 3+ , In 3+ and As 3+ induced a marked emission quenching (see Fig.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…The LOD were in the mM range and were similar to those calculated for other recently published probes for trivalent cations. [9][10][11][12][13][14][15][16][17][18][19][20][21] Moreover, we also found that water-acetonitrile 95 : 5 v/v solutions of 3 showed, when excited at 300 nm, an intense emission band at 397 nm. From all the cations tested, only the addition of Cr 3+ , Fe 3+ , Al 3+ , Ga 3+ , In 3+ and As 3+ induced a marked emission quenching (see Fig.…”
mentioning
confidence: 78%
“…7 For these reasons, the development of optical chemosensors able to discriminate trivalent from divalent and monovalent cations 8 is especially appealing. In particular, there are relatively few probes able to detect simultaneously several trivalent cations [9][10][11][12][13][14][15][16][17][18][19] and we have found in the literature only one probe that recognizes Al 3+ , Fe 3+ , Cr 3+ , As 3+ , In 3+ and Ga 3+ at the same time. 20 Moreover, most probes for trivalent cations display sensing features in organic solvents and it is rare to find probes for these cations in pure water.…”
mentioning
confidence: 99%
“…Similar to the other chemodosimeters, probe 76 has been successfully applied to detect intracellular Fe 3+ ions in live RAW264.7 cells by fluorescence microscopy. Adopting the hydrolytic cleavage of imine linkage, the multi-analytes selective chemodosimeter 77 has been developed for the detection of trivalent metal ions (Fe 3+ , Cr 3+ , and Al 3+ ) in THF-H 2 O (8:2) medium [86]. The strong Lewis acidity of trivalent cations (Fe 3+ /Al 3+ /Cr 3+ ) selectively breaks the imine linkage, resulting in significant fluorescence enhancement at 430 nm (λ exc = 330 nm).…”
Section: Fluorescent Chemodosimeters For Fe(iii)mentioning
confidence: 99%
“…Even though several fluorescent probes are available for the detection of divalent or trivalent ions, probes useful for the collective detection of trivalent metal ions are very few in number. In the last couple of years, few reports based on 4 the chemosensors for trivalent metal ion detection are published in various international journals [29][30][31][32][33][34]. Most of these fluorescent probes operate based on metal ion induced fluorescence 'turn-on' or 'turn-off' mechanisms.…”
Section: Introductionmentioning
confidence: 98%